O-10 Palliative medicine specialist training: designing and implementing an oncology placement fit for the future. (20th March 2022) - Westwood, Peter; Schuberth, Anna; Gillon, Suzie; Hurlow, Adam
Abstract : Background: Palliative Medicine trainees in Yorkshire and the Humber undertake a largely observational Oncology rotation. A successful pilot of proactive early palliative care (PC) input was conducted in an Acute Oncology Assessment Unit (OAU) leading to the initiation of a PC in-reach service, provided by PC registrars, with the aims of improving patient care and learning (including curriculum fulfilment) for trainees. Aims: Determine educational learning opportunities afforded by the pilot Assess impact of the in-reach service on trainees Consider if this model could fit the development of the new Internal and Palliative Medicine curriculum Methods: PC registrars provided input on the OAU, initially through a pilot period, then in an established in-reach service. Appropriate patients were identified by Oncology staff and PC registrars. PC intervention consisted of a face-to-face review or verbal advice. The learning opportunities were documented and service provision was mapped to the draft Palliative Medicine Curriculum 2022 'capabilities in practice' (CiPs). Results: Pilot: 41 referrals: 32 face-to-face reviews; 9 advice In-reach service: 44 additional referrals: 28 face-to-face reviews; 16 advice Diverse disease– and treatment-related presentations Referrals for symptom control, ACP/information needs, psychological support and liaison with community and hospital palliative care teams The clinical experiences and competencies developed can be mapped to generic and specialty specific (including Internal Medicine) CiPs. All PC registrars felt it improved the Oncology rotation; increasing exposure to relevant acute medical and oncological presentations. Conclusion: Through a successful pilot, the Yorkshire & Humber oncology placement has been adapted to incorporate an in-reach service in the acute oncology setting. This rich learning environment has been beneficial for trainees, and is also likely to be beneficial for patients. This in-reach model aids the achievement of current curriculum competencies and could be of value for achieving Internal and Palliative Medicine competencies.